Impact of Shifting Cultivation on Dense Tropical Woodlands in Southeast Angola. (December 2015) - Wallenfang, Johannes; Finckh, Manfred; Oldeland, Jens; Revermann, Rasmus
Dry tropical woodlands are the characteristic natural vegetation type of southeast Angola, where precipitation is seasonal and nutrient content of soils is very low. Subsistence farmers overcome the poor abiotic conditions by using shifting cultivation based on specific site selection. We describe the vegetation composition of a previously unstudied dense woodland tract, which is preferred for agriculture, comparing it to nearby open woodland. We placed 25 vegetation plots randomly in the two types of natural woodland vegetation (open and dense) as well as in fallows with three different durations of land use. In each plot the cover of all vascular plant species was recorded. Variables describing vegetation structure, including basal area and leaf area index, were recorded. We analyzed soil samples for texture, pH, conductivity and nutrients, and investigated the impact of land use duration on woodland regeneration. We found that species composition and vegetation structure of the dense woodland differed greatly from the surrounding open woodland. The dense woodland is preferable for agriculture because of its higher soil content of silt, clay and potassium, higher woody biomass, and more abundant soft litter. A longer duration of land use affects species composition and diversity of the regenerating vegetation as well as nutrient content in the soil. In the near future, the increasing demand for agricultural land is likely to change the structure and composition of the dense woodland.